Water-resistant catalyst as well as preparation method and application thereof
The In2O3-InPdx/m-ZrO2-SiO2 catalyst solves the problem of insufficient thermochemical stability of the existing catalyst hydrophobic strategy, realizes efficient CO2 hydrogenation to methanol reaction, and improves methanol selectivity and catalyst stability.
Patent Information
- Application Number
- CN202510716314.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-09
AI Technical Summary
Existing catalyst hydrophobic treatment strategies in the CO2 hydrogenation to methanol reaction have problems such as insufficient thermochemical stability, organic residues covering active sites, mass transfer limitations and high regeneration costs, making it difficult to meet industrial needs.
The In2O3-InPdx/m-ZrO2-SiO2 catalyst is used. By loading indium, palladium and In2O3 on the m-ZrO2-SiO2 carrier, the low polarity and rich oxygen vacancies of amorphous SiO2 are utilized to increase the difficulty of water molecules infiltration, thereby promoting the positive shift of the chemical equilibrium of the methanol production reaction.
The methanol selectivity and catalyst stability are significantly improved, the service life of the catalyst is extended, and the adverse effects of water molecules on the reaction are reduced.
Smart Images

Figure CN120605715A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalyst preparation methods, and in particular to a water-resistant catalyst and its preparation method and application. Background Art
[0002] CO2 hydrogenation technology has become one of the core paths to achieve carbon recycling because it can directly convert CO2 into high-value-added chemicals or fuels. This technology can not only alleviate dependence on fossil energy, but also build a zero-carbon chemical system by coupling renewable energy to produce hydrogen (green hydrogen). Methanol (CH3OH) is an efficient energy carrier and multifunctional platform chemical, widely used in energy, chemical and other fields; and because of its unique physicochemical properties and a wide range of application scenarios, CH3OH, as the most promising C1 platform molecule, is regarded as a key medium for achieving carbon neutrality goals. Catalytic hydrogenation of CO2 to produce methanol can not only achieve "carbon cycle closure", but also alleviate the methanol industry's dependence on fossil raw materials.
[0003] The CO2 hydrogenation reaction to produce methanol is as follows:
[0004] CO2(g)+3H2(g)→CH3OH(g)+H2O ΔH θ 298K =–49.01 kJ·mol -1
[0005] Accompanied by the reverse water gas shift (RWGS) side reaction:
[0006] CO2(g)+H2(g)→CO(g)+H2O ΔH θ 298K =41.17 kJ·mol -1
[0007] The reverse water-gas shift reaction, as a competitive side reaction, forms a fierce game with the methanol synthesis pathway, resulting in a decrease in the selectivity of the target product. Kinetically, water molecules (H2O) generated during the reaction are easily adsorbed on the catalyst surface, which not only inhibits the progress of the main reaction through chemical equilibrium but also may induce oxidation or sintering of active sites, aggravating catalyst deactivation and seriously affecting the long-term use of the catalyst.
[0008] Currently, hydrophobic treatment of catalysts is mostly focused on copper-based catalysts, and the commonly used hydrophobic reagents are long-chain organic reagents such as silane coupling agents, long-chain carboxylic acids, polymers, etc. The inherent defects exposed in actual reactions have seriously restricted the industrialization process of catalysts. Although the above hydrophobic strategies can improve methanol selectivity on a laboratory scale, they are difficult to meet the stability and economic requirements of industrial catalysts due to key issues such as insufficient thermochemical stability, coverage and mass transfer restrictions of organic residues on active sites, blockage of pores on the catalyst surface, and high regeneration costs. The above problems highlight the unsustainability of traditional organic reagent hydrophobic strategies. Summary of the Invention
[0009] The present invention provides a water-resistant catalyst and a preparation method and application thereof, so as to solve the technical problem that the catalyst hydrophobic strategy in the prior art is unsustainable.
[0010] To achieve the above object, the technical solution provided by the present invention is as follows:
[0011] The first aspect of the present invention provides a water-resistant catalyst, wherein the catalyst is In2O3-InPd x / m-ZrO2-SiO2, that is, indium, palladium and In2O3 are loaded on the m-ZrO2-SiO2 carrier, wherein the loading ratio of indium, palladium and In2O3 is 4.5~7.5:2.7~5:0.4~3.4.
[0012] Furthermore, the particle size of the catalyst is 120 nm to 180 nm.
[0013] The second aspect of the present invention provides a method for preparing the above-mentioned water-resistant catalyst, comprising the following steps: S1, hydrolyzing tetraethyl orthosilicate, adding m-ZrO2 and ultrasonically treating, stirring, centrifuging, drying, and calcining to obtain m-ZrO2-SiO2; S2, dissolving a soluble salt of indium and a soluble salt of palladium, adding the m-ZrO2-SiO2 and co-impregnating, stirring, drying, and calcining, and then introducing a reducing gas for reduction to obtain the catalyst In2O3-InPd x / m-ZrO2-SiO2.
[0014] Furthermore, in the step S1, the weight ratio of the tetraethyl orthosilicate to the m-ZrO2 is 1.25 to 10:1.
[0015] Furthermore, in step S1, the stirring temperature is 80°C to 100°C, and the stirring time is 12h to 48h; the calcination temperature is 500°C to 600°C, and the calcination time is 6h to 8h.
[0016] Furthermore, in step S2, the molar ratio of the soluble salt of indium to the soluble salt of palladium is 1 to 3:1; and the weight ratio of the soluble salt to the m-ZrO2-SiO2 is 0.515 to 0.376:1.
[0017] Furthermore, in step S2, the calcination temperature is 300° C. to 400° C., and the calcination time is 3 h to 5 h.
[0018] Furthermore, in step S2, hydrogen is introduced to reduce the calcined material, the reduction reaction temperature is 200° C. to 500° C., the hydrogen flow rate is 30 to 60 mL / min, and the holding time is 1 h to 3 h.
[0019] Furthermore, the step of hydrolyzing tetraethyl orthosilicate in step S1 includes: mixing tetrapropylammonium hydroxide, water, anhydrous ethanol, and tetraethyl orthosilicate in a weight ratio of 4.62:37.92:27.2:1.875-15, and stirring at room temperature for 3h-6h to fully hydrolyze the tetraethyl orthosilicate.
[0020] Furthermore, the preparation method of m-ZrO2 includes the following steps: dissolving a soluble salt of zirconium and performing a hydrothermal reaction, drying and calcining the precipitate after centrifugation to obtain the m-ZrO2.
[0021] Furthermore, the soluble salt of zirconium is selected from one or more of zirconyl nitrate and zirconyl dichloride; the temperature of the hydrothermal reaction is 130°C to 180°C, and the reaction time is 6h to 10h; the calcination temperature is 250°C to 450°C, and the calcination time is 3h to 5h.
[0022] The third aspect of the present invention provides the use of the above-mentioned water-resistant catalyst in the catalytic hydrogenation of CO2 to methanol.
[0023] The water-resistant catalyst provided by the present invention can prolong the wetting time of water molecules on the catalyst surface, increase the difficulty of water molecule wetting, thereby reducing the adverse effects of water molecules on the catalytic reaction, and can promote the positive shift of the chemical equilibrium of the methanol formation reaction, thereby achieving higher methanol selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments recorded in this application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1TEM image and elemental mapping of the catalyst in Example 1;
[0026] Figure 2 The XRD patterns of the catalysts in Examples 1 to 4 and Comparative Example 2 are shown;
[0027] Figure 3 The catalyst water drop contact angle test results of Examples 1 to 4 and Comparative Example 1 are shown;
[0028] Figure 4 The graphs of CO2 conversion and methanol selectivity versus temperature for the catalysts of Examples 1 to 4 when used in the CO2 catalytic hydrogenation to methanol reaction are shown;
[0029] Figure 5 The graphs of the space-time yields of the catalysts of Examples 1 to 4 used in the CO2 catalytic hydrogenation to methanol reaction as a function of temperature are shown;
[0030] Figure 6 This is a comparison chart of CO2 conversion and methanol selectivity as a function of temperature in the CO2 catalytic hydrogenation reaction to produce methanol using the catalysts of Example 1 and Comparative Example 1;
[0031] Figure 7 This is a graph showing the CO2 hydrogenation stability test results of the catalyst in Example 1. DETAILED DESCRIPTION
[0032] In order to help those skilled in the art better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making any creative efforts shall fall within the scope of protection of this application.
[0033] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the conditions under which this application can be implemented. Therefore, they have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed in this application without affecting the efficacy and purpose that can be achieved by this application.
[0034] In the first aspect of the embodiment of the present application, a water-resistant catalyst is provided, the catalyst being In2O3-InPd x / m-ZrO2-SiO2, i.e., indium, palladium, and In2O3 are loaded on an m-ZrO2-SiO2 carrier, wherein the loading ratio of indium, palladium, and In2O3 is 4.5-7.5:2.7-5:0.4-3.4. Furthermore, the catalyst particle size is 120 nm to 180 nm.
[0035] In the embodiments of the present application, ZrO2 has abundant oxygen vacancies, balanced acid-base sites, good stability, and can also optimize the electronic structure of the catalyst through metal-support interaction; m-ZrO2 will have more oxygen vacancies and is more effective in regulating metal-support interaction. Amorphous SiO2, as a pure silicon material, is composed only of low-polarity Si-O-Si bonds and does not require highly hydrophilic cations to compensate for the charge, resulting in a lower overall polarity of the material. In addition, the surface of the pure silicon material lacks sufficient hydroxyls or cations as hydrogen bond acceptors, and it is difficult for water molecules to interact with the material through hydrogen bonds. Therefore, by combining m-ZrO2 and amorphous SiO2 to prepare water-resistant m-ZrO2-SiO2 as a catalyst carrier, In2O3-InPd x / m-ZrO2-SiO2 catalyst exhibits water resistance.
[0036] The embodiment of the present application uses inorganic amorphous SiO2 to treat the In-Pd intermetallic compound catalyst for water resistance, ensuring that the water molecules are more difficult to infiltrate after treatment, reducing the adverse effects of water molecules on the catalytic reaction, promoting the chemical equilibrium of the methanol formation reaction to move forward, and improving the selectivity of methanol. x The difficulty of wetting on the / m-ZrO2-SiO2 catalyst is significantly increased, which not only shifts the chemical equilibrium of the methanol formation reaction to the positive direction, improves the methanol selectivity, but also effectively inhibits the catalyst deactivation. At the same time, thanks to the structural stability of amorphous SiO2, the catalyst In2O3-InPd x / m-ZrO2-SiO2 can still exist stably under high temperature and high pressure, and still maintains good catalytic performance after 100 hours of continuous operation.
[0037] The second aspect of the embodiment of the present application provides a method for preparing the above-mentioned water-resistant catalyst, comprising the following steps: S1, hydrolyzing tetraethyl orthosilicate, adding m-ZrO2 and ultrasonically treating, stirring, centrifuging, drying, and calcining to obtain m-ZrO2-SiO2; S2, dissolving a soluble salt of indium and a soluble salt of palladium, adding m-ZrO2-SiO2 for co-impregnation, stirring, drying, and calcining, and then introducing a reducing gas for reduction to obtain a catalyst In2O3-InPd x / m-ZrO2-SiO2.
[0038] In the embodiment of the present application, m-ZrO2-SiO2 was prepared by secondary growth method, and In2O3-InPd was prepared by wet impregnation. x The m-ZrO2-SiO2 catalyst has a simple and easy preparation method and readily achievable preparation conditions. The amount of tetraethyl orthosilicate significantly influences the catalyst's water resistance, as amorphous SiO2 is key to the catalyst's water resistance. The amount of tetraethyl orthosilicate directly affects the amorphous SiO2 content in the m-ZrO2-SiO2 catalyst. Specifically, increasing the amount of tetraethyl orthosilicate increases the amorphous SiO2 content, thereby enhancing water resistance.
[0039] In some embodiments, the weight ratio of tetraethyl orthosilicate to m-ZrO2 is 1.25 to 10:1. In the embodiments of the present application, while the amount of m-ZrO2 remains unchanged, adjusting the amount of tetraethyl orthosilicate can adjust the relative content of m-ZrO2 and SiO2 in the m-ZrO2-SiO2, thereby correspondingly adjusting the water resistance of the catalyst.
[0040] Specifically, in step S1, the stirring temperature is 80°C to 100°C, and the stirring time is 12h to 48h; the calcination temperature is 500°C to 600°C, and the calcination time is 6h to 8h. In the embodiment of the present application, the stirring temperature affects the stirring time and the distribution of SiO2. When the stirring temperature is low, a longer stirring time is required to achieve effective combination of m-ZrO2 and SiO2; when the stirring temperature is high, local supersaturation triggers random nucleation of SiO2 particles, resulting in uneven distribution of SiO2. In addition, if the calcination temperature is too low, the template (tetrapropylammonium hydroxide) will remain and block the pores; and if the temperature is too high, it may cause the pores to collapse or the structure to shrink, significantly reducing the specific surface area and pore volume.
[0041] In some embodiments, in step S2, the molar ratio of the soluble salt of indium to the soluble salt of palladium is 1 to 3:1; the weight ratio of the soluble salt to m-ZrO2-SiO2 is 0.376 to 0.515:1. In the embodiment of the present application, indium, palladium and In2O3 are loaded on the m-ZrO2-SiO2 carrier, and the indium and palladium exist in the form of InPd x The relative content of the loaded phases can be controlled by varying the amounts of indium and palladium soluble salts. When the molar ratio of indium to palladium soluble salts is 2:1, the catalyst exhibits the best catalytic performance.
[0042] In some embodiments, in step S2, the calcination temperature is 300°C to 400°C, and the calcination time is 3 hours to 5 hours. In the embodiments of the present application, a calcination temperature that is too high can cause the active components of the catalyst to agglomerate and increase the particle size, ultimately affecting the catalytic activity of the catalyst; a calcination temperature that is too low can result in insufficient decomposition of the precursor.
[0043] In some embodiments, in step S2, hydrogen is introduced to reduce the calcined material. The reduction reaction temperature is 200°C to 500°C, the hydrogen flow rate is 30 to 60 mL / min, and the holding time is 1 hour to 3 hours. In the embodiments of the present application, under the above temperature conditions, 10% hydrogen is added to reduce the calcined catalyst, so that the final catalyst is loaded with indium, palladium, and In2O3 on the carrier m-ZrO2-SiO2.
[0044] In some embodiments, the step of hydrolyzing tetraethyl orthosilicate in step S1 includes mixing tetrapropylammonium hydroxide, water, anhydrous ethanol, and tetraethyl orthosilicate in a weight ratio of 4.62:37.92:27.2:1.875-15, and stirring at room temperature for 3-6 hours to fully hydrolyze the tetraethyl orthosilicate. In this embodiment of the present application, tetrapropylammonium hydroxide serves as a template to provide a pore structure for SiO2; water and anhydrous ethanol serve as solvents, which facilitate the dissolution and hydrolysis of tetrapropylammonium hydroxide and tetraethyl orthosilicate, forming a uniform precursor solution.
[0045] In the embodiments of the present application, m-ZrO2 can be commercially available or prepared by the following method. The preparation method of m-ZrO2 comprises the following steps: dissolving a soluble salt of zirconium and performing a hydrothermal reaction, centrifuging, drying, and calcining the precipitate to obtain m-ZrO2. m-ZrO2 is prepared by a hydrothermal method, repeatedly centrifuging until no chloride ions are detected, and calcining to obtain m-ZrO2.
[0046] Specifically, the soluble zirconium salt is selected from one or more of zirconyl nitrate and zirconyl dichloride. The hydrothermal reaction temperature is 130°C to 180°C, and the reaction time is 6 hours to 10 hours. The calcination temperature is 250°C to 450°C, and the calcination time is 3 hours to 5 hours.
[0047] The third aspect of the embodiments of the present application provides the use of the above-mentioned water-resistant catalyst or the water-resistant catalyst prepared by the above-mentioned preparation method in the catalytic hydrogenation of CO2 to produce methanol.
[0048] The water-resistant catalyst of the embodiment of the present application is used for catalytic hydrogenation of CO2 to produce methanol. It can prolong the wetting time of water molecules on the catalyst surface and increase the difficulty of water molecules infiltration, thereby reducing the adverse effects of water molecules on the catalytic reaction, and can promote the positive movement of the chemical equilibrium of the methanol production reaction, thereby achieving higher methanol selectivity.
[0049] All reagents in the following examples are commercially available.
[0050] Example 1
[0051] A water-resistant catalyst, the catalyst is In2O3-InPd x / m-ZrO2-SiO2, that is, indium, palladium and In2O3 are loaded on the m-ZrO2-SiO2 carrier, wherein the loading ratio of indium, palladium and In2O3 is 4.5:3:3.4.
[0052] The preparation method of the water-resistant catalyst comprises the following steps:
[0053] 1. Prepare m-ZrO2 by hydrothermal method. Prepare 0.5 mol / L ZrOCl2·8H2O solution using deionized water and salt and maintain it at 150℃ for 8 hours in a Teflon-lined hydrothermal reactor. Repeatedly centrifuge the white precipitate until no Cl is detected using AgNO3 / HNO3 solution (1.0 mol / L). - Then, the sample was dried in an oven at 110 °C for 12 h and calcined at 350 °C (heating rate of 5 °C / min) for 4 h to obtain m-ZrO2.
[0054] 2. Prepare the m-ZrO2-SiO2 composite support by the secondary growth method. Prepare a mixed solution according to the dosage of 4.62g tetrapropylammonium hydroxide (TPAOH), 37.92g deionized water, 27.2g anhydrous ethanol and 7.5g tetraethyl orthosilicate (TEOS). Stir the mixed solution at room temperature for 5h to ensure that TEOS is fully hydrolyzed. Add 1.5g of m-ZrO2 to the above mixed solution, then perform ultrasonic treatment and stir at 95℃ for 24h. Separate the solid and liquid by centrifugation, dry the solid at 100℃ for 12h, and then calcine at 550℃ (heating rate of 1℃ / min) for 8h to obtain m-ZrO2-SiO2.
[0055] 3. Preparation of In2O3-InPd by wet impregnation x / m-ZrO2-SiO2 catalyst. 0.1532g In(NO3)3·5H2O and 0.0555g Pd(NO3)2·xH2O were dissolved in 1mL deionized water, and then 0.5g m-ZrO2-SiO2 was added. The sample was stirred thoroughly for 1h and then transferred to an oven to dry at 100℃ overnight. The dried sample was calcined at 300℃ for 3h in a muffle furnace, and after calcination, the sample was kept reduced in a 10% hydrogen atmosphere (50mL / min) at 300℃ for 1h to obtain In2O3-InPd x / m-ZrO2-SiO2.
[0056] The In2O3-InPd prepared in this example xThe Mg / m-ZrO₂-SiO₂ catalyst was characterized using TEM (Talos F200X). High-angle annular dark-field scanning transmission electron microscopy (HAADF STEM) was used to complement the energy-dispersive spectroscopy (EDS) analysis of the elemental distribution maps. The microscope was operated at an accelerating voltage of 200 kV. Powder samples were dispersed in anhydrous ethanol and then dropped onto copper grids.
[0057] Characterization results reference Figure 1 Characterization results showed that the catalyst particle size ranged from 120 nm to 180 nm. A high degree of overlap between Zr and Si was observed in the elemental mapping, confirming the successful preparation of the m-ZrO2-SiO2 support. Metallic indium and palladium were densely and evenly distributed on the m-ZrO2-SiO2 support. Indium oxide could not be effectively distinguished in the elemental mapping.
[0058] Example 2
[0059] This embodiment is substantially the same as embodiment 1, except that the amount of tetraethyl orthosilicate (TEOS) in step 2 is replaced with 1.875 g.
[0060] Example 3
[0061] This embodiment is substantially the same as embodiment 1, except that the amount of tetraethyl orthosilicate (TEOS) in step 2 is replaced with 3.75 g.
[0062] Example 4
[0063] This embodiment is substantially the same as embodiment 1, except that the amount of tetraethyl orthosilicate (TEOS) in step 2 is replaced with 15 g.
[0064] Comparative Example 1
[0065] This comparative example is basically the same as Example 1, except that in step 3, m-ZrO2-SiO2 is replaced by m-ZrO2 to obtain the catalyst In2O3-InPd x / m-ZrO2.
[0066] Comparative Example 2
[0067] This comparative example is basically the same as Example 1, except that in step 3, m-ZrO2-SiO2 is replaced by SiO2 to obtain the catalyst In2O3-InPd x / SiO2.
[0068] Figure 2 The XRD pattern of the catalyst showed that InPd xand In2O3 diffraction peaks, so Comparative Example 2 is composed of indium, palladium and In2O3; in Examples 1 to 4, the diffraction peaks of the carrier m-ZrO2 appear, which shows that SiO2 is amorphous. In addition, only InPd x The diffraction peaks of m-ZrO2 and In2O3 overlap, so the diffraction peak of In2O3 cannot be detected. However, since the only difference between Examples 1 to 4 and Comparative Example 2 is the carrier, it can be confirmed that Examples 1 to 4 are composed of indium, palladium, and In2O3.
[0069] Using a contact angle meter ( The water resistance of the catalysts in Examples 1 to 4 and Comparative Example 1 was tested. The testing method was as follows: a certain amount of catalyst was placed on the instrument stage, 2 μL of deionized water was added dropwise, and the contact angle was recorded using a camera. The water molecule infiltration process was recorded to obtain the water molecule infiltration time.
[0070] Test results reference Figure 3 As can be seen from the figure, the water contact angles of the catalysts in Examples 1 to 4 were 16° to 18°, and the residence time of water on the catalyst surface was significantly extended to 4s to 23s. In contrast, the water contact angle of the catalyst in Comparative Example 1 was 15°, and the residence time of water on the catalyst surface was only 1.2s. These results demonstrate that the water resistance of the catalysts in Examples 1 to 4 is enhanced.
[0071] The In2O3-InPd prepared in Examples 1 to 4 x / m-ZrO2-SiO2 catalyst and In2O3-InPd prepared in Comparative Example 1 x / m-ZrO2 catalyst is used in the reaction of catalytic hydrogenation of CO2 to methanol. The specific reaction steps are as follows:
[0072] The performance of the CO2 hydrogenation catalyst was evaluated in a fixed-bed reactor. First, 0.15 g of catalyst (40-60 mesh) was mixed with 0.35 g of quartz sand. After the temperature was raised to the reaction temperature under an inert atmosphere, a H2 / CO2 mixture (H2 / CO2 volume ratio of 3:1) was introduced and the pressure was increased to 4 MPa, with a GHSV of 8000 mL / g. cat / h. The temperature evaluation range was 230℃~310℃, with a temperature interval of 20℃. The product gas stream was analyzed (CH3OH, CO, CH4 and CO2) by gas chromatograph (SCION, 456C). CO2 conversion rate (X CO2 ) and CH3OH selectivity (S CH3OH ) is calculated as follows:
[0073] X CO2 =(1-(f CO2 A CO2,out) / (f CO2 A CO2,in ))×100
[0074] S CH3OH =(f CH3OH A CH3OH,out ) / (f CO2 A CO2,in -f CO2 A CO2,out )×100
[0075] Where f and A represent the chromatographic peak area and the correction factor of the corresponding substance, respectively.
[0076] The STY calculation formula of CH3OH is as follows:
[0077] STY=(μ CO 2×X CO2 ×S CH3OH ×M CH3OH ) / (m cat ×V m )
[0078] Among them, μ CO 2 is the flow rate of CO2 (L / h), X CO2 is the conversion rate of CO2, S CH3OH is the selectivity of CH3OH, M CH3OH represents the molecular weight of CH3OH (32.04 g / mol), m cat is the mass of the catalyst (g), V m is the molar volume of CO2 under standard conditions (22.4 L / mol).
[0079] Figure 4 The graphs of CO2 conversion and methanol selectivity versus temperature for the catalysts of Examples 1 to 4 when used in the CO2 catalytic hydrogenation to methanol reaction are shown; Figure 5 The graphs of the space-time yields of the catalysts of Examples 1 to 4 used in the CO2 catalytic hydrogenation to methanol reaction as a function of temperature are shown. Figure 4 It can be seen that the CO2 conversion rate changes with the amount of TEOS used in each embodiment, showing a trend of first increasing and then decreasing. The CO2 conversion rate of Example 1 is the highest. Figure 5 It can be seen that the selectivity of methanol in Example 1 is the highest, and the yield of methanol is also the highest, reaching the best conversion rate of 3.10 mmol / g at 270 °C. cat / h.
[0080] From the above results, it can be seen that there is an optimal value for the amount of TEOS used. Too weak or too strong water resistance of the catalyst will have an adverse effect on the conversion of CO2 and the production of methanol.x The amount of TEOS in the / m-ZrO2-SiO2 catalyst is the optimal amount, achieving the best balance between water resistance and reaction results.
[0081] Figure 6 The following graph compares the CO2 conversion rate and methanol selectivity as a function of temperature in the CO2 catalytic hydrogenation to methanol reaction using the catalysts of Example 1 and Comparative Example 1. As can be seen from the comparison in the figure, the catalyst of Example 1 exhibits high methanol selectivity, achieving a methanol selectivity of 54% even at 310°C. In contrast, the methanol selectivity of Comparative Example 1 rapidly drops to 42%. This demonstrates that the highly water-resistant m-ZrO2-SiO2 support effectively prevents water molecules from residing and infiltrating on the catalyst surface, thereby significantly reducing the water molecule concentration on the catalyst surface and promoting a positive shift in the chemical equilibrium of the methanol production reaction.
[0082] The catalyst of Example 1 was tested for CO2 hydrogenation stability. Figure 7 As can be seen from the figure, within 100 hours of reaction, the CO2 conversion rate did not change much with the reaction time, while the methanol selectivity slowly increased and eventually remained above 80%. This verifies that the catalyst of the embodiment has excellent stability and good application prospects.
[0083] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A water-resistant catalyst, characterized in that: The catalyst is In2O3-InPd x / m-ZrO2-SiO2, that is, indium, palladium and In2O3 are loaded on the m-ZrO2-SiO2 carrier, wherein the loading ratio of indium, palladium and In2O3 is 4.5~7.5:2.7~5:0.4~3.
4.
2. The water-resistant catalyst according to claim 1, characterized in that The particle size of the catalyst is 120nm to 180nm.
3. The method for preparing a water-resistant catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1. Hydrolyze tetraethyl orthosilicate, add m-ZrO2 and ultrasonicate, stir, centrifuge, dry and calcine to obtain m-ZrO2-SiO2; S2, dissolving the soluble salt of indium and the soluble salt of palladium, adding the m-ZrO2-SiO2 for co-impregnation, stirring, drying and calcining, and then introducing reducing gas for reduction to obtain the catalyst In2O3-InPd x / m-ZrO2-SiO2.
4. The method for preparing a water-resistant catalyst according to claim 3, wherein: In the step S1, the weight ratio of tetraethyl orthosilicate to m-ZrO2 is 1.25 to 10:1; and / or, In the step S1, the stirring temperature is 80° C. to 100° C., and the stirring time is 12 hours to 48 hours; the calcination temperature is 500° C. to 600° C., and the calcination time is 6 hours to 8 hours.
5. The method for preparing a water-resistant catalyst according to claim 3, wherein: In the step S2, the molar ratio of the soluble salt of indium to the soluble salt of palladium is 1 to 3:1; and the weight ratio of the soluble salt to the m-ZrO2-SiO2 is 0.376 to 0.515:
1.
6. The method for preparing a water-resistant catalyst according to claim 3, wherein: In step S2, the calcination temperature is 300° C. to 400° C., and the calcination time is 3 h to 5 h; and / or, In the step S2, hydrogen is introduced to reduce the calcined material. The reduction reaction temperature is 200° C. to 500° C., the hydrogen flow rate is 30 to 60 mL / min, and the holding time is 1 to 3 hours.
7. The method for preparing a water-resistant catalyst according to any one of claims 3 to 6, characterized in that: The step of hydrolyzing tetraethyl orthosilicate in step S1 includes: mixing tetrapropylammonium hydroxide, water, anhydrous ethanol, and tetraethyl orthosilicate in a weight ratio of 4.62:37.92:27.2:1.875-15, and stirring at room temperature for 3h-6h to fully hydrolyze the tetraethyl orthosilicate.
8. The method for preparing a water-resistant catalyst according to any one of claims 3 to 6, characterized in that: The preparation method of m-ZrO2 comprises the following steps: dissolving a soluble salt of zirconium and performing a hydrothermal reaction, drying and calcining the precipitate after centrifugation, thereby obtaining the m-ZrO2.
9. The method for preparing a water-resistant catalyst according to claim 8, wherein: The soluble salt of zirconium is selected from one or more of zirconyl nitrate and zirconyl dichloride; the temperature of the hydrothermal reaction is 130°C to 180°C, and the reaction time is 6h to 10h; the calcination temperature is 250°C to 450°C, and the calcination time is 3h to 5h.
10. Use of the water-resistant catalyst according to claim 1 or 2, or the water-resistant catalyst prepared by the preparation method according to any one of claims 3 to 9, in catalytic hydrogenation of CO2 to produce methanol.